Perinatal mental ill health: the experiences of women from ethnic minority groups. (2nd October 2019) - Watson, Helen; Soltani, Hora
Abstract : Objectives: This study aimed to investigate ethnic minority women's experiences and opinions of perinatal mental health problems and the provision support services. Methods: An exploratory survey was undertaken using a questionnaire. Quantitative data were analysed using descriptive statistics and a simple thematic analysis was used for the qualitative data. A total of 51 responses from women of 14 different ethnic minority backgrounds were analysed. Findings: Women from minority ethnic groups face barriers to seeking help for perinatal mental ill health as a result of ongoing stigma, the poor attitudes and behaviours of health professionals and inappropriately designed services. Conclusions: Future interventions should focus on providing adequate cultural competency for health professionals and ensure that all women are able to access culturally appropriate spaces to talk and be listened to in community settings and wider services.